The effects of player substitutions on match winning performance in Turkish Super League - Halit Egesoy; Hayrettin Gumusdag; Mertcan Ebubekir Cimbilaz; Yavuz Ihsan Kilic (ROL Spor Bilimleri Dergisi)
During the soccer game, coaches have to make strategic decisions on player substitutions. Player substitutions made at the right time and with the right player can have a significant impact on winning the competition. The aim of this study is to investigate the effects of player substitutions in Turkish Super League competitions on match winning performance. The sample of the present study was composed of 100 matches randomly selected from the Turkish Professional Soccer League (Super League) during the 2020-2021 season. A total of 766 player substitutions made by the home and away teams in these competitions were analyzed according to the determined parameters. All the data obtained were given and interpreted as frequency and percentage values. As a result of the analyzes carried out, it was determined that the first player substitutions occurred mostly in the half-time and between 46-60 minutes of the competitions. It was found that the second player substitutions occurred mostly between the 61-75 minutes of the games. It has been observed that the third, fourth and fifth substitutions are mostly made between the 76-90 minutes of the matches. As a result, the fact that the coaches make more substitutions, especially between the 61-90 minutes of the matches, can be explained as the result of a strategy they apply to win the match by interfering with the game. In addition, coaches' substitutions time strategies can have an impact on the game tactics applied during the competition and final outcome in the match.